2010
DOI: 10.1097/00003643-201006121-00059
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cost effectiveness using low flow anesthesia with an oxygen/nitrous oxide carrier gas sevoflurane versus using high flow anesthesia with an oxygen/nitrous oxide carrier gas sevoflurane during 2 hours anesthesia in abdominal surgery

Abstract: Background and Goal of Study:Interventional radiology (IR) came of age with the medical profession's desire to develop minimally invasive therapies1. Some of these procedures cause significant patient discomfort, and yet require relative patient immobility for optimal results calling for an increasing need for sedation and anaesthesia. Our study aimed to assess the provision of sedation service in IR. Materials and Methods: 101 radiology departments in acute hospital trusts in England and Wales responded to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…This study found that the cost and consumption of sevoflurane in group 1 were significantly less than that in group 2. Our result was similar to previous studies 4,7,8 that reported that sevoflurane expenditure and costeffectiveness were significantly reduced in low-flow anesthesia patients. On the other hand, when the lower FGF was used, more exhaled CO 2 passed through the CO 2 absorbent, resulting in an increased consumption of CO 2 absorbent.…”
Section: Cost and Consumption Of Sevoflurane And Litholymesupporting
confidence: 93%
See 1 more Smart Citation
“…This study found that the cost and consumption of sevoflurane in group 1 were significantly less than that in group 2. Our result was similar to previous studies 4,7,8 that reported that sevoflurane expenditure and costeffectiveness were significantly reduced in low-flow anesthesia patients. On the other hand, when the lower FGF was used, more exhaled CO 2 passed through the CO 2 absorbent, resulting in an increased consumption of CO 2 absorbent.…”
Section: Cost and Consumption Of Sevoflurane And Litholymesupporting
confidence: 93%
“…The sample size per group was 32, which was calculated using two independent means formulas: the two-tailed significance of 0.01 and the power of 0.9 based on previous data. 4 Because a drop-out rate of 10% was expected, the desired sample size was 35 subjects per group. The sample size required for this study was 70 patients.…”
Section: Sample Size Calculation and Statistical Analysismentioning
confidence: 99%
“…Sevoflurane is currently the most commonly used volatile anesthetic, and its use is uniquely increased in pediatric anesthesia due to the amount of inhalational inductions performed. A 2010 study from Albania demonstrated a significant decrease in the amount and cost of sevoflurane when using 1L FGF vs 4.5L FGF with sevoflurane in adults undergoing elective abdominal surgery lasting at least 2 hours 1 . This study demonstrated the cost‐saving potential of low‐flow anesthesia but did not quantify any environmental effect.…”
Section: Introductionmentioning
confidence: 87%
“…Nitrous oxide (N2O) is the most used inorganic inhalational anaesthetic due to its proven pharmacokinetic properties and low cost (0.80€/L). The use of an inorganic gas with anaesthetic properties as N2O, allows to reduce the costs per operation, by reducing the amount of volatile halogenated hydrocarbons necessary to induce the anaesthetic state, which are significantly more expensive (Isoflurane -126€/L, sevoflurane -756€/L, Desflurane -806€/L) [12][13][14][15].…”
Section: Background and Motivationmentioning
confidence: 99%
“…Therefore, the anaesthetic gas commonly used is nitrous oxide (N2O), due to its low cost (0.80 €/L). Moreover, the use of N2O allows to reduce the costs per operation, by reducing the amount of volatile anaesthetics necessary to induce the anaesthetic state, which are significantly more expensive (Isoflurane -126 €/L, sevoflurane -756 €/L, Desflurane -806 €/L) [12][13][14][15]. Other approach to reduce the costs is to rebreathe the remainder inhalational anaesthetics, performing the operation in a closedcircuit mode.…”
Section: Introductionmentioning
confidence: 99%